Rational case management of malaria with a rapid diagnostic test, Paracheck Pf®, in antenatal health care in Bangui, Central African Republic - Manirakiza Alexandre; Serdouma Eugène; Heredeïbona Luc; Djalle Djibrine; Madji Nestor; Moyen Methode; Soula Georges; Le Faou Alain; Delmont Jean (BMC, 2012)
Abstract Background Both treatment and prevention strategies are recommended by the World Health Organization for the control of malaria during pregnancy in tropical areas. The aim of this study was to assess use of a rapid diagnostic test for prompt management of malaria in pregnancy in Bangui, Central African Republic. Methods A cohort of 76 pregnant women was screened systematically for malaria with ParacheckPf® at each antenatal visit. The usefulness of the method was analysed by comparing the number of malaria episodes requiring treatment in the cohort with the number of prescriptions received by another group of pregnant women followed-up in routine antenatal care. Results In the cohort group, the proportion of positive ParacheckPf® episodes during antenatal clinics visits was 13.8%, while episodes of antimalarial prescriptions in the group which was followed-up routinely by antenatal personnel was estimated at 26.3%. Hence, the relative risk of the cohort for being prescribed an antimalarial drug was 0.53. Therefore, the attributable fraction of presumptive treatment avoided by systematic screening with ParacheckPf® was 47%. Conclusions Use of a rapid diagnostic test is useful, affordable and easy for adequate treatment of malaria in pregnant women. More powerful studies of the usefulness of introducing the test into antenatal care are needed in all heath centres in the country and in other tropical areas.